Efektifitas Assesment Kompetensi Perawat Manager terhadap Kinerja Perawat - Hermayanti, Hermayanti (Journal of Comprehensive Science, 2025)
Nurse career development, particularly in the transition from clinical to managerial roles, requires effective competency assessments and performance assessments. This study aims to analyze the relationship between competency assessment and performance assessment in supporting nurse career development. The method used is a literature review using the PICOS framework. Of the 242 articles found, 20 articles were selected for analysis. The results show that competency assessment can improve the quality of nursing services, while professional indicator-based performance assessment helps identify the strengths and weaknesses of nurses. This research also highlights the importance of managerial competence, leadership, and informatics in supporting nurses' career development. In conclusion, the integration of competency assessment and performance assessment is an effective strategy to improve nurse competence and health service quality. This research makes an important contribution to the development of nursing science and practical recommendations for hospital management, nursing education institutions, and policymakers to design integrated professional development programs.